Multidimensional regulation of transcription factors: decoding the comprehensive signals of plant secondary metabolism - Li, Hongwei; Chen, Nana; Zhang, Hongbin; Xu, Delin (Frontiers in Plant Science, 2025)
Plants synthesize an extensive array of secondary metabolites in response to diverse biotic and abiotic stresses. These metabolites function not only as defensive compounds but also constitute significant sources of nutrition and pharmaceuticals. However, the mechanisms governing the synthesis of these secondary metabolites have long been a central focus of research and continue to pose significant challenges. Transcription factors (TFs), serving as key regulators of secondary metabolite synthesis in plants, exhibit mechanisms of action that are still not fully understood. This review summarizes the latest research advancements on how plant transcription factors mediate the regulation of secondary metabolite biosynthesis through various signaling pathways, including light signaling, hormone signaling, MAPK signaling, the ubiquitin-proteasome pathway, epigenetic regulation, microbial interactions, and climate change. A deeper understanding of the mechanisms regulating transcription factors is expected to provide new insights into the biosynthesis of plant secondary metabolites.